THE URBAN ECOLOGY DALAM RANGKA PENINGKATAN ENVIRONMENTAL AWARENESS DI KELURAHAN BIDARA CINA JAKARTA TIMUR - Damianus Dai Koban (Program Studi Manajemen Lingkungan, 2020)
The research aims to find out how the application of Urban Ecology in order to increase Environmental Awareness in East Jakarta Bidara Cina. The method used is theoretical descriptive method. The study was conducted from January to May 2018. The results showed that there are four obstacles in the application of Urban Ecology in order to increase Environmental Awareness in East Jakarta Bidara namely, first the need for land for urban residents is very large, so that green space becomes the main obstacle limitation land, both the urbanization of the immigrant population causing the population to increase from year to year so that, the land is more limited, the third the number of young people who are not aware of the environment, so as not to support the movement of environmental awareness, the four busyness of religious leaders causing the lack of worship activities so that socialization on environmental awareness is not done maximally.